Внешняя политика С. Стамболова и правительств Народно-либеральной «стамболовистской» партии Болгарии в оценке советской историографии периода НЭПА и Сталинского режима - Миколенко, Д.В. (Българска академия на науките, 2014)
This paper considers the trends and attitudes of the soviet historians of the New Economic Policy and Stalin’s regime to the study of Stambolov’s foreign policy, and policy of the People’s Liberal (Stambolovist) Party governments. The evaluation of the international position of S. Stambolov and the People’s Liberal (Stambolovist) Party governments by soviet authors was dependent on the interpretation of the Russian foreign policy in the late 19th - early 20th century by historians. The author concludes that such important components of the subject, as an attempt to resolve in favor of Sofia the Macedonian issue and Bulgaria‘s relationships with the neighboring Balkan countries, were lost, which are omitted due to more detailed illumination of its relations with the great countries.
Keywords: Стамболов С.; Богария